POSITION UNIVERSITY STUDENTS TO E-LEARNING - Milan, KLEMENT (Trends in education, 2010)
The paper presents the views and attitudes of university students on issues of e-learning as one of modern methods of education in undergraduate studies. Presents the progress and results of an investigation, which ran from 2005 to 2009.
Keywords: e-learning; research; survey research; quantitative research; statistical methods; Pearson's chi-square.